(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
In today’s fast-paced world, social media plays a crucial role in everyone’s life, influencing both the positive and negative aspects of their daily balance. This article explores the effects of social media on all age groups. It highlights several negative consequences such as mental health issues, anxiety, low self-esteem, sleep disorders, high stress, and even depression.